Impact of Local Anesthesia on Wound Healing - Maha T. Al-Saffar1 , Abdulsattar Salim Mahmood2 , Mohammed Salih Sulaiman3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Different local anesthetics produce multiple effects on wound healing, although this effect did notdemonestrated clearly in experimental study. This study aimedto evaluate the effects of several localanesthetics (lidocaine, articaine, mepivacaine) on healing of oral mucosal wound healing in experimentalrabbits by histological examination.The study was conducted on eight healthy adult male New Zealandwhite rabbits which divided into four group(n=2) control group which received no treatment group two(received lidocaine 2% with adrenalin) group three (received mepivacaine) and group four (receivedarticaine 4%). oral mucosal wound were initiated experimentally in all group and each group received theirtreatment by local application one time daily for six day(except control group) in the third day half of theanimal were sacrificed in each group and histological examination for the wound area were conducted , theremaining animal were sacrificed in the sixth day of treatment and histological examination were made forthe wound area to compare the result between the four group. The mepivacaine group produce better result(enhance healing of the oral mucosal wound) followed by atricaine and lidocaine group compared withcontrol one. This study showed that different type of local anesthesia produces different effects on woundhealing manufisted histologically and clinically.